2010
DOI: 10.1152/japplphysiol.01411.2009
|View full text |Cite
|
Sign up to set email alerts
|

Calculating alveolar capillary conductance and pulmonary capillary blood volume: comparing the multiple- and single-inspired oxygen tension methods

Abstract: Key elements for determining alveolar-capillary membrane conductance (Dm) and pulmonary capillary blood volume (Vc) from the lung diffusing capacity (Dl) for carbon monoxide (DlCO) or for nitric oxide (DlNO) are the reaction rate of carbon monoxide with hemoglobin (thetaCO) and the DmCO/DlNO relationship (alpha-ratio). Although a range of values have been reported, currently there is no consensus regarding these parameters. The study purpose was to define optimal parameters (thetaCO, alpha-ratio) that would ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 32 publications
6
52
0
Order By: Relevance
“…This value is derived from the solubility and the molecular weight of the gases (3). Others have determined a ratio of 2.2 to 2.4 (9,47). It has been determined that a ratio of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This value is derived from the solubility and the molecular weight of the gases (3). Others have determined a ratio of 2.2 to 2.4 (9,47). It has been determined that a ratio of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that this correction factor ranges from 1.93 to 2.49; specifically, more recent work by Ceridon et al has demonstrated that a correction factor of 2.11 is most appropriate with exercise studies and as such used in this study (Ceridon et al 2010).…”
Section: Protocolmentioning
confidence: 95%
“…Another variable is the DM,NO/DM,CO ratio (a) which, on physical principles, should be in the range 1.93-1.97. Investigators have ''forced'' a to 2.42 [17] or 2.08-2.26 [18] to give a ''best fit'' with the DM,CO and Vc calculated from the oxygen two-step Roughton-Forster TL,CO method. Since a is defined as the physical diffusivity ratio of NO/CO, this approach cannot be correct physiologically.…”
Section: Dmco and Vc From Simultaneous Single Breathmentioning
confidence: 99%